Sistem Dan Simulasi Deteksi Banjir Untuk Peringatan Dini Diolah Memakai Metode KNN Berbasis Arduino - Felix Stanley; Erick Alfons Lisangan (Fakultas Teknologi Informasi, Universitas Atma Jaya Makassar, 2020)
In the city of Makassar, flooding is one of natural disasters that has a high probability of occurring and has very large impact. Floods occur due to several factors such as increased rainfall and rising sea levels. Flooding in the city of Makassar is an annual natural disaster that has huge impact for people who live around the river. The purpose of this study is to predict and provide early warning of floods before the flood occurs using water flow and KNN algorthm. The result of this research is an early detection system and a simulation to predict flood that has 60% accuracy.